The Effectiveness of Digital Classroom Learning in Improving Students' Learning Outcomes in Islamic Religious Education at MIN 7 Banda Aceh - Khadijah Khadijah; Muslem Daud; Rahmadon Rahmadon (Lembaga Teewan Journal Solutions, 2026)
The development of information technology has accelerated significantly in recent years. This condition has been positively embraced by the field of education through the integration of technology into teaching and learning processes. Numerous studies have been conducted to examine the benefits of educational technology in supporting educational stakeholders, including students, in achieving successful learning outcomes. The present study aimed to investigate the effectiveness of digital classroom learning in improving students' learning outcomes in Religious Education subjects at Madrasah Ibtidaiyah Negeri (MIN) 7 Banda Aceh. The sample of this study consisted of one digital classroom group comprising 32 students, selected from a population of 96 students distributed across three digital classes. To collect data on students' learning achievement, achievement tests were administered in four Religious Education subjects, namely Al-Qur'an and Hadith, Fiqh, Aqidah Akhlaq, and Islamic Cultural History (Sejarah Kebudayaan Islam/SKI). The test instruments were reviewed and verified by a panel of Religious Education teachers to ensure the content validity and reliability of the instruments. The findings revealed that the digital classroom students achieved exceptionally high academic performance, with all students surpassing the Minimum Mastery Criterion (Kriteria Ketuntasan Minimal/KKM) threshold of 80 points. Furthermore, nearly 100% of the students obtained a perfect score of 100 on the Al-Qur'an and Hadith achievement test, based on a grading scale ranging from 0 to 100. It can therefore be concluded that digital classroom learning is effective in enhancing students' learning outcomes in Religious Education subjects at Madrasah Ibtidaiyah Negeri (MIN) 7 Banda Aceh.